2004
DOI: 10.1128/jvi.78.7.3792-3796.2004
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of Neutralizing Human Monoclonal Antibodies against Human Immunodeficiency Virus Type 1 Tat Antigen

Abstract: The human immunodeficiency virus Tat regulatory protein is essential for virus replication and pathogenesis. From human peripheral blood mononuclear cells of three Tat toxoid-immunized volunteers, we isolated five Tat-specific human monoclonal antibodies (HMAbs): two full-length immunoglobulin G (IgG) antibodies and three single-chain fragment-variable (scFv) antibodies. The two IgGs were mapped to distinct epitopes within the basic region of Tat, and the three scFvs were mapped to the N-terminal domain of Tat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
(35 reference statements)
2
11
0
Order By: Relevance
“…Neutralization was detectable only at low dilution of sera and this was mainly due to the polyclonal nature of antibodies present in the tested sample. In contrast, anti-Tat monoclonal antibodies have been shown to exhibit high neutralizing capacity at very high dilutions [22,33]. These findings extend previous observations showing that another TLR ligand, the Mycoplasma-derived macrophage-activating lipopeptide-2 (recognized by TLR-2), is a potent adjuvant when coadministered with Tat intranasally [21].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Neutralization was detectable only at low dilution of sera and this was mainly due to the polyclonal nature of antibodies present in the tested sample. In contrast, anti-Tat monoclonal antibodies have been shown to exhibit high neutralizing capacity at very high dilutions [22,33]. These findings extend previous observations showing that another TLR ligand, the Mycoplasma-derived macrophage-activating lipopeptide-2 (recognized by TLR-2), is a potent adjuvant when coadministered with Tat intranasally [21].…”
Section: Discussionsupporting
confidence: 85%
“…Both dsRNA motifs potentiated the anti-Tat antibody responses, which were comparable to those elicited in the presence of CT. Analysis of the fine-specificity of anti-Tat IgG antibodies using synthetic peptides revealed strong reactivity with peptides 1-20 and 44-61, which represent important epitopes [10,[19][20][21][22][31][32][33][34][35]. However, only sera of mice immunized with sTat and pI:pC motif inhibited Tat-driven transactivation.…”
Section: Discussionmentioning
confidence: 99%
“…In 1988, Krone et al identified the NT as the major binding site of natural anti-HIV-1 Tat Abs (49). Later, it was shown that Ab responses targeting this conserved epitope (50) are able to neutralize Tat-dependent transactivation in vitro (51)(52)(53). Overall, Tat-specific immune responses in humans were linked to lower viral loads and delayed disease progression (54)(55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…These results extend previous observations demonstrating the immunodominance of these epitopes after intranasal immunization [24,25] and suggest that sTat is processed and presented by epidermal Langerhans cells (LC) the same way as by the dendritic cells of the mucosal epithelium. These epitopes are generally conserved and play a critical role in the cellular uptake of Tat and transactivation [26][27][28][29]. Moreover, anti-Tat antibodies elicited after transcutaneous immunization neutralized Tat-driven transactivation, demonstrating the potential of this route to elicit antibodies that bind to extracellular Tat, which conceivably are capable of inhibiting its deleterious effects.…”
Section: Discussionmentioning
confidence: 99%
“…It is composed of 86-101 amino acid residues (depending on the isolate) encoded by two exons. The first 72 amino acid residues (encoded by the first exon) are organized into three functional domains: (i) an acidic N-terminal region (aa [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] that binds to cell surface CD26 and is thought to mediate immunosuppressive activity [3]; (ii) a cysteine-rich domain (aa [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] that mediates binding to chemokine receptors [4]; and (iii) the basic domain (aa 41-60). The latter domain is responsible for the internalization of extracellular Tat and its import into the nucleus and is also required for binding to short RNA transcripts containing the viral transactivation-responsive element (TAR) [5,6].…”
Section: Introductionmentioning
confidence: 99%